Examining low-income community health service utilization based on spatial design and proximity a case study on Barangay Matina community healthcare facilities - Niosco, Royden Dominic T.; Juanga, Jean Marie V. (2023)
This case study focuses on the utilization of health services in low-income communities in Barangay Matina, Davao City. It examines the accessibility of healthcare facilities, their physical condition, and the perceptions of residents regarding facility design and services. The study also explores the relationship between facility design, proximity to healthcare services, and healthcare utilization. The research aims to identify factors influencing health-seeking behavior and improve healthcare provision for low-income populations. It utilizes a quantitative research design, including surveys and interviews, with a sample size of 200 households. Data analysis involves descriptive statistics and correlation tests. The study's findings provide insights into healthcare service perceptions and design quality, comparing different facility locations. The results contribute to the development of design guidelines for low-income community healthcare and inform recommendations for improving accessibility and quality of healthcare services in marginalized communities.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2023